Microbiome-metabolome analysis reveals alterations in the composition and metabolism of caecal microbiota and metabolites with dietary Enteromorpha polysaccharide and Yeast glycoprotein in chickens - Wassie, Teketay; Cheng, Bei; Zhou, Tiantian; Gao, Lumin; Lu, Zhuang; Xie, Chunyan; Wu, Xin (Frontiers in Immunology, 2022)
The intestinal microbiome is responsible for the fermentation of complex carbohydrates and orchestrates the immune system through gut microbiota-derived metabolites. In our previous study, we reported that supplementation of Enteromorpha polysaccharide (EP) and yeast glycoprotein (YG) in combination synergistically improved antioxidant activities, serum lipid profile, and fatty acid metabolism in chicken. However, the mechanism of action of these polysaccharides remains elusive. The present study used an integrated 16S-rRNA sequencing technology and untargeted metabolomics technique to reveal the mechanism of action of EP+YG supplementation in broiler chickens fed basal diet or diets supplemented with EP+YG (200mg/kg EP + 200mg/kg YG). The results showed that EP+YG supplementation altered the overall structure of caecal microbiota as evidenced by β diversities analysis. Besides, EP+YG supplementation caused microbiota dysbiosis by altering the caecal microbiota community profile at the phylum and genus levels. Furthermore, Spearman correlation analysis indicated a significant correlation between altered microbiota genera vs serum cytokine levels and microbiota genera vs volatile fatty acids production. Predicted functional analysis showed that EP+YG supplementation significantly enriched amino acid metabolism, nucleotide metabolism, glycan biosynthesis and metabolism, energy metabolism, and carbohydrate metabolism. Metabolomics analysis confirmed that EP+YG supplementation modulates a myriad of caecal metabolites by increasing some metabolites, including pyruvic acid, pyridoxine, spermidine, spermine, and dopamine, and decreasing metabolites related to lipid metabolisms such as malonic acid, oleic acid, and docosahexaenoic acid. The quantitative enrichment analysis results further showed that glycolysis/gluconeogenesis, citric acid cycle, tyrosine metabolism, glycine, serine, and threonine metabolism, and cysteine and methionine metabolism were the most important enriched pathways identified with enrichment ratio >11, whereas, fatty acid biosynthesis and biosynthesis of unsaturated fatty acids pathways were suppressed. Together, the 16S-rRNA and untargeted metabolomics results uncovered that EP+YG supplementation modulates intestinal microbiota and their metabolites, thereby influencing the important metabolism pathways, suggesting a potential feed additive.